Perception of young employees on working relationships with older employees at Bank Simpanan Nasional and Affin Bank in Selangor - Azhana, A. Aziz (2017)
Working satisfaction is one of the most important topics that need to be addressed. Currently, increasing number of young employees in the workforce is attracting more benefits for the organizations. With the new era of workforce involving different demographic background, working in team could lead to lower satisfaction in workplace. The main purpose of this study is to investigate the perception on working relationship with older employees in term of communicative teamwork, mutual learning and communicating feedback towards working satisfaction in Bank Simpanan Nasional and Affin Bank in Selangor. The population of the study is limited to the young employees’ who age 40 years and below working at Bank Simpanan Nasional and Affin Bank in Selangor with the total population of 240 employees. Data analysis/statistical method used in this study are descriptive analysis, reliability test, normality test, multiple regression and Pearson’s correlation analysis. A total of 103 respondents participated in the study. The response rate for this study was 51.5% with 103 returned questionnaires. Data were analyzed using SPSS 20.0. The theory used in this study is Communication Accommodation Theory (CAT). CAT considers that communicators that are members of different social groups may influence interpersonal communication. The result showed that there is a significant relationship between communicative teamwork, communicating feedback and mutual learning towards working satisfaction.